“Ethical Behavior of Millennial and Gen Z Accountants: Behavioral Accounting Study in 2025" - Amin Sadiqin (Journal of Economics, Management, Accounting, Business, Educational, Technology, and Social Science, 2025)
This research aims to examine the ethical behavior of millennial and Gen Z accountants in Indonesia, especially in the context of the accounting profession in 2025. With the increasing development of technology and social change, the younger generation, including millennials and Gen Z, face new challenges in maintaining their professional integrity. This research uses a quantitative approach with a survey method among millennial and Gen Z accountants who work in various accounting sectors. The results showed significant differences in ethical attitudes between the two groups, with factors such as education, exposure to technology, and work experience influencing their ethical decisions. These findings can be a consideration for educational institutions, regulators and professional organizations to develop policies that support the development of better ethical behavior among the younger generation of accountants.